INFLATION AND COMPANY FINANCE. - Mathews, Russell (The Accounting Review, 1960)
The great inflation of the last twenty years has caused, if not a revolution in accounting thought, at least a civil war among accountants. It is not possible in this paper to examine the reasons for this failure among accountants to agree on a course of action that will avoid the pitfalls of conventional practice. In particular, since accounting is primarily a process of classification and measurement, it is necessary to agree on what the accounts are designed to measure and how the measurement may best be carried out. The need for relatively easy measurement is stressed because many of the solutions that are advanced to deal with the price level problems, while reasonably meeting conceptual or theoretical requirements, seem altogether too complicated to apply in practice. One of the major reasons for the confusion that has resulted from the price-level controversy, and the failure of accountants and economists to agree on remedial action, has been the attempt by nearly everyone engaged in the argument to find a unique measure of business surplus-one that will be suitable for all purposes and acceptable to all parties making use of accounting data.